Enhancement of dielectric and electro-optical parameters of a newly prepared ferroelectric liquid crystal mixture by dispersing nano-sized copper oxide. Issue 2 (26th January 2020) - Khan, Sidra; Chauhan, Shikha; Chandran, Achu; Czerwiński, Michał; Herman, Jakub; Biradar, Ashok M.; Prakash, Jai
ABSTRACT: Here, we present the effect of copper (II) oxide nanoparticles (nCuO) on dielectric and electro-optical parameters of a newly prepared ferroelectric liquid crystal (FLC) mixture, namely W302. The FLC mixture, comprising of pyrimidine compounds, was characterised through dielectric spectroscopy, differential scanning calorimetry (DSC), polarising optical microscopy (POM) and other electro-optical methods. The material parameters such as spontaneous polarisation, rotational viscosity, response time and tilt angle of W302 were found to be 14 nC/cm 2, 240 mPa.s, 150 µs and 28 ᴼ, respectively. The phase transition temperatures of W302 were observed through DSC and further confirmed by the dependence of dielectric loss factor in homogeneously aligned FLC sample with temperature. We also demonstrate the observance of a low-frequency dielectric relaxation mode due to the unwinding of the helix, called as partially unwound helical mode ( p -UHM) along with Goldstone mode. The behaviour of p -UHM has been systematically studied with temperature and applied bias field. Further, dispersion of nCuO into host W302 has shown a significant increase in dielectric permittivity. Also, the p -UHM relaxation peak in the dielectric regime has disappeared with the incorporation of nCuO. These studies would be useful to fabricate better electro-optical devices for display, switching and beam steering applications. The formulation and characterization of a ferroelectric liquid crystal (FLC) mixture W302 composed of pyrimidine compounds is presented. Then, we observed the effect of copper (II) oxide nanoparticles (nCuO) on dielectric and electro-optical parameters of a newly prepared and characterized FLC mixture. Graphical Abstract: uf0001